Environment and Social Commitment Plan (ESCP) - International Center for Tropical Agriculture (Accelerating Impacts of CGIAR Climate Research for Africa, 2024)
This Environment and Social Commitment Plan (ESCP) has been developed for the Accelerating Impacts of CGIAR Climate Research for Africa (AICCRA) Additional Financing (AF) project. This additional funding is outlined in a new agreement with the World Bank (WB) and will be applied exclusively to added activities within the project, while the original ESCP continues to cover the initial project aspects. The ESCP is a legal document between the WB and CIAT on Environment and Social (E&S) requirements relative to the AICCRA AF. It defines mandatory measures, actions, timelines, institutional arrangements, training, monitoring, reporting, and grievance management that the International Center for Tropical Agriculture (CIAT) must adhere to. It also specifies the E&S instruments that are to be implemented, subject to consultation, disclosure, and approval by the WB. Lastly, the ESCP is subject to revision based on adaptive management, project changes, unforeseen circumstances, or performance feedback. The execution of the AICCRA project is led and coordinated by the CIAT, with additional support from various CGIAR centers. As the leading entity, CIAT has prepared this ESCP to adhere to its commitment to project safeguard requirements and to align with global best practices in E&S management.